Retypification of the name Eryngium palmatum (Apiaceae) - Kuzmanović, Nevena; Clementi, Moreno; Kabaš, Eva; Vukojičić, Snežana (Phytotaxa, 2013)
Eryngium palmatum was described by Roberto de Visiani and Josif Pančić in Plantae serbicae rariores aut novae (1870: 20). Wörz (2010) stated that, although the original description is from 1870, Pančić recorded E. tricuspidatum Linnaeus (1753: 8) eleven years earlier with the same localities that Visiani and he cited in the protologue for E. palmatum. In fact, Pančić reported E. tricuspidatum already in 1856: 520, for the following localities: “bei Ravanita, Sv. Petka im Cupriaer, Banja im Aleksinacer, Ugljarevo im Kragujevacer“. Describing the new species E. palmatum in 1870, Visiani and Pančić cited all the previously mentioned localities with the addition of mt. Ogradjenik: “Hab. in saxosis calcareis prope Ravanica, Sv. Petka in circ. Cupria, ad Banja circ. Aleksinac, Uljarevo circ. Kragujevac, et mont. Ogradjenak Serbiae meridionalis”.